2015
DOI: 10.4103/1305-7456.163222
|View full text |Cite
|
Sign up to set email alerts
|

The influence of type 2 diabetes mellitus on salivary matrix metalloproteinase-8 levels and periodontal parameters: A study in an Indian population

Abstract: Objective:Although many studies reported more severe periodontal disease and the existing proinflammatory conditions in patients with diabetes but only few have examined the effect of type 2 diabetes mellitus (DM) on salivary matrix metalloproteinase-8 (MMP-8) level and other periodontal parameters. This study aims to evaluate the effect of type 2 DM on salivary MMP-8 levels and periodontal parameters, which might be useful in monitoring periodontal disease in diabetes.Materials and Methods:A total of 90 subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 35 publications
(35 reference statements)
4
12
0
Order By: Relevance
“…In our study, periodontal status was recorded using CPI, following which oral exfoliative cytology Our study showed that diabetes patients had a significant higher CPI score and loss of attachment than control group which was similar to results obtained by Kim et al, [14] Radhika and Ranganathan, [15] Popławska-Kita et al, [16] Das et al, [17] Prakash et al, [18] and Gupta et al [19] in their studies. This higher CPI clearly denotes that they have a higher incidence of periodontitis, probably because there is alteration in chemotaxis of neutrophils and, moreover, diabetics have compromised local immunity which aggravated the periodontal damage.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, periodontal status was recorded using CPI, following which oral exfoliative cytology Our study showed that diabetes patients had a significant higher CPI score and loss of attachment than control group which was similar to results obtained by Kim et al, [14] Radhika and Ranganathan, [15] Popławska-Kita et al, [16] Das et al, [17] Prakash et al, [18] and Gupta et al [19] in their studies. This higher CPI clearly denotes that they have a higher incidence of periodontitis, probably because there is alteration in chemotaxis of neutrophils and, moreover, diabetics have compromised local immunity which aggravated the periodontal damage.…”
Section: Discussionsupporting
confidence: 89%
“…We found that MMP-8 increases in patients who are diabetic as compared to control which is in accordance with the study of Kumar et al (28) who reported a significant increase in gingival tissue MMP 8 level in diabetic patients having chronic periodontitis as compared to controls. Another study by Gupta et al (29) also reported a rise in salivary MMP-8 levels as compared to nondiabetic controls. In our study, MMP-8 was also elevated in smokers with chronic periodontitis as compared to the control, which is consistent with the finding of Liu et al (30) who investigated MMP-8 expression by immunofluorescence staining in periodontal tissue samples of smokers and nonsmokers.…”
Section: Discussionmentioning
confidence: 87%
“…In previous experimental study, following these periodontal pathogen exposure, the absence of TLR2 had been accompanied by increased mortality, although the precise mechanisms of TLR2 involvement in host defense have not been identified. [ 17 18 19 ] Activation of proinflammatory cytokine, release of huge numbers of leukocyte migration, and direct antimicrobial action of innate immunity induced by TLRs may play a major role of massive dilatation of blood vessel,[ 20 ] increased level of reactive oxygen species,[ 21 ] and end with damage to host cells. [ 22 ]…”
Section: Discussionmentioning
confidence: 99%